FACTORS AFFECTING NIGHT ECONOMY DEVELOPMENT: A CASE STUDY IN DA NANG CITY, VIETNAM - Tuan Anh LE; Vu Phan Gia ANH; Tram Nguyen Thi HUYEN; Nguyen Minh Quan HA (Geo Journal of Tourism and Geosites, 2023)
The purpose of this study is to examine the factors affecting the development of the night economy in Da Nang city, Vietnam on the basis of a survey of 346 domestic tourists choosing this as a tourist destination and participate in night activities and services. The author has synthesized the relevant background theory as well as previous outstanding studies on the issue of tourism development and night economy. SPSS 20 software was used to test the relationship between factors affecting the development of the night economy based on the viewpoints of tourists, residents and local authorities. The results of the study show that 05 factors affect the development of the night economy in Da Nang city in order: The development of a variety of services; Legal and safety regulations; cultural experience opportunities; infrastructure and traffic; service prices. The remaining two factors did not find any influence on the development of the night economy: tourism natural resources; promote and share. The study once again confirms the relationship between the factors affecting the development of the night economy and is a document to help researchers understand better in the research context in Vietnam, one of the leading countries in the world. developing countries and are limited in developing the night economy after the Covid-19 pandemic.